2001
DOI: 10.1136/bjo.85.6.732
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ocular melanocyte and uveal melanoma cell invasion and the implication of α1β1, α4β1 and α6β1 integrins

Abstract: Background/aims-Posterior uveal melanoma is the most common intraocular tumour in adults, responsible for the death of approximately 35% of patients. Hepatic metastases are most frequent, and once diagnosed survival is usually less than 1 year. The 1 family of integrins, v 3 and MMP-2 and MMP-9 have been implicated in the metastasis of several types of tumour. To study their involvement in uveal melanoma we analysed the expression of the 1 integrins, v 3, MMP-2, and MMP-9 in 10 primary posterior uveal melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
2
29
0
2
Order By: Relevance
“…13 In this present study, a similar pattern of a1-and a4-expression was observed between invasive and noninvasive cells (Table 2), while lower levels of a6-expression were detected on noninvasive cells when compared with their invasive counterparts (Table 2). Together, these data support an involvement of these receptors with malignant progression and the invasive phenotype previously demonstrated.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…13 In this present study, a similar pattern of a1-and a4-expression was observed between invasive and noninvasive cells (Table 2), while lower levels of a6-expression were detected on noninvasive cells when compared with their invasive counterparts (Table 2). Together, these data support an involvement of these receptors with malignant progression and the invasive phenotype previously demonstrated.…”
Section: Discussionsupporting
confidence: 63%
“…Expression of ICAM-1 has been associated with an increased risk of uveal melanoma metastasis 15 and worse prognosis in cutaneous melanoma, 4,32 and similarly invasive cells studied here expressed higher levels than their noninvasive counterparts (Table 2), also implicating an involvement of ICAM-1 in invasion. As described previously, both uveal melanocytes 13 and noninvasive cells do not express a4-integrins, while increased levels were detected on invasive cells (Table 2). Although little is known about a4-integrins and uveal melanoma metastasis, ligation of a4b1 with its endothelial ligand VCAM-1 is involved with cutaneous melanoma metastasis, 7 and the pattern of spread is proposed to relate to organ-specific VCAM-1 expression.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations